Isolation and characterization of psychrotolerant denitrifying bacteria for improvement of nitrate removal in woodchip bioreactors treating agricultural drainage water at low temperature. Issue 2 (23rd December 2021) - Jéglot, Arnaud; Schnorr, Kirk Matthew; Sørensen, Sebastian Reinhold; Elsgaard, Lars
Abstract : Nitrate removal was enhanced by the addition of isolated and pre-grown psychrotolerant denitrifiers at low temperature (5 °C). Abstract : Denitrifying woodchip bioreactors are used at field-scale to remove nitrate from agricultural drainage water before it contaminates aquatic ecosystems. However, low microbial activity at cold temperatures during the winter half-year may cause the efficiency of nitrate removal to drop below 20%. Here, we isolated 134 strains of denitrifying bacteria from woodchips and wetland soil to search for candidates for bioaugmentation to improve nitrate removal at cold temperatures. The strains were identified by analyses of 16S rRNA genes and were dominated by Pseudomonadaceae ( n = 63), notably the genus Pseudomonas ( n = 58). Two candidates for bioaugmentation, P. proteolytica WBRS105 and P. chlororaphis PSS4, were selected among six strains that were characterized in detail by assays of growth and denitrification at 5 and 10 °C, combined with genome analysis. Both strains possessed the genes for complete denitrification and degradation of carbon substrates such as cellulose, hemicellulose and lignin. Also, both strains were able to grow with extracts from woodchips as sole sources of energy and carbon. Bioaugmentation under laboratory conditions indicated that the two strains were able to compete with an established microbial community in enrichment cultures at 5 °C and enhance nitrate removal rates by 27–37% when applied to woodchips from an operating full-scale bioreactor. The successful bioaugmentation of woodchip microbiomes at low temperature is encouraging, although the increased rate obtained under laboratory conditions should be further tested, e.g., under pilot-scale conditions, to verify the potential of the technology to increase the efficiency of bioreactors treating agricultural drainage water.